Relationship between Internet Addiction, Personality Factors, and Emotional Distress among Adolescents in Malaysia - Soh Chou Fu; Nicholas Tze Ping Pang; Walton Wider (Children, 2022)
COVID-19 has significantly affected the mental health of adolescents, thus increasing the emotional distress among them. Studies have reported that heavy Internet use during COVID-19 was linked with poor mental health among adolescents. Additionally, it was found that personality factors are linked with mental health in general. Although past literature has reported the effect of personality factors on mental health, there are limited studies examining the underlying mechanisms among Malaysian adolescents. Therefore, the current study offers an understanding of the intervening role of personality factors in the relationship between Internet addiction and emotional distress among adolescents in Malaysia. This study also aimed to determine the prevalence of Internet addiction and emotional distress (depression, stress, and anxiety) among adolescents in Malaysia. There are a total of 500 participants from 7 secondary schools who range from 13 to 19 years of age. This was a cross-sectional study, and 3 valid questionnaires were used: The Internet Addiction Test (IAT), the Depression, Anxiety, and Stress Scale (DASS-21), and the Ten-Item Personality Inventory (TIPI). Partial least square structure equation modelling (SmartPLS) was used to analyse the mediation models. The results showed that the prevalence of Internet addiction among adolescents was 29.6% and the prevalence of depression, anxiety, and stress among adolescents were 64.8%, 78%, and 51.4%, respectively. Furthermore, mediation analysis showed only emotional stability mediated the relationship between Internet addiction and emotional distress, but not openness to experience, extraversion, conscientiousness, or agreeableness. It is proposed that mental health providers should focus on providing emotion-related interventions to adolescents confronting COVID-19 challenges, ultimately improving mental health.